The effect of health analysis competency on results of laboratory in the microscopic referral health center in Surabaya - NURUSYSYARIFAH ALIYYAH; VEBBY AMELLIA EDWIN; TJIPTO RINI (International Journal of Pharma and Bio Sciences, 2019)
The Microscopic Referral Health Center (MRHC) Tuberculosis (TB) is a laboratory that is capable of making preparations, coloring, and microscopic examination of phlegm. It receives referrals and conducts technical coaching to the Satellite Health Center (SHC) and health workers. The development of health workers is expected to work in accordance with the education and skill they have and establish competent health personnel to ensure the accuracy of microscopic phlegm results. This research was carried out in all Microscopic Referral Health Centers (MRHC) in Surabaya between February 2013 and January 2014. The sample in this study was the Microscopic Referral Health Center (PRM) health analyst in Surabaya who had participated in microscopic Tuberculosis (TB) training and had been certified. The results of data analysis using ANOVA test showed that: i) the Fcount value was 4,638 with a significance level of 0.030 which is less than 5% in preparation,ii) the Fcount value was 11,573 with a significance level of 0.01 less than 5% in the process and iii) the Fcount value was 4,603 with a significance level of 0.031 less than 5% on reading. This proves that there is a significant influence between the competence of health analysts on preparation, process, and reading of the results of Ziehl – Neelsen (ZN) direct preparations.